Good Practice under bad conditions? Multi-level dependency and municipal capacity to act in dealing with heterogenization and participation in Halle (Saale) - Kullmann, Katharina (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
Municipal capacity to act in addressing social heterogenization is increasingly dependent on structural interdependencies within multi-level governance. Using the East German medium-sized city of Halle (Saale) as a case study, this paper examines how issues of social heterogenization and participation are addressed at the local level, in light of the city’s context-specific development and its dependence on higher governance levels. While the local turn discussed in the literature often emphasises the autonomous scope of action of cities, the analysis shows how local action in Halle (Saale) is constrained as that of a post-transformational, financially weak municipality dependent on external funding. Based on 22 qualitative interviews, it is reconstructed how the municipality, in cooperation with local non-state actors, organises long-term work in the context of temporary funding structures and dependency within multi-level governance. The city is capable of acting through early network formation and the advocacy work of local intermediary organisations. However, this capacity is based on a precarious economy of chained funding and unpaid labour, which leads to the exhaustion of local structures. The paper concludes that under current conditions, a persistent “stop-and-go” pattern of social policy interventions emerges.
Keywords: Local governance; Local turn; Integration policy; Multi-level governance analysis; European Social Fund; Halle (Saale)